The NLRP3 inflammasome in urogenital cancers: structure, dual function, and therapeutic potential - Sun, Weiming; Ma, Ruiting; Zhao, Rui; Tian, Jiaju; Liu, Wenhui (Frontiers in Oncology, 2025)
The NLRP3 inflammasome is a multi-subunit complex consisting of the NLRP3 receptor protein, apoptosis-associated speck-like protein (ASC), and the effector protein caspase-1. The activation mechanisms of the NLRP3 inflammasome are diverse and complex, primarily involving both classical and non-classical pathways. The activation process is generally considered to occur in two stages: the first, “priming,” which involves the initial immune signaling trigger, followed by the second stage, “activation,” during which further signaling leads to the formation and functional activation of the NLRP3 inflammasome. Upon activation, the NLRP3 inflammasome activates caspase-1, triggering the maturation and release of downstream pro-inflammatory cytokines, such as IL-18 and IL-1β, which in turn promote the inflammatory response. In recent years, an increasing body of research has highlighted the close association between the NLRP3 inflammasome and its downstream signaling pathways with the development and progression of urogenital system cancers. These studies suggest that the NLRP3 inflammasome may serve as a potential therapeutic target, holding significant clinical application value in cancer treatment. Despite the growing number of related studies, a comprehensive and systematic review summarizing the role of the NLRP3 inflammasome in urogenital cancers and its potential therapeutic strategies is still lacking. This review aims to provide an extensive overview of the composition and activation mechanisms of the NLRP3 inflammasome, explore its involvement in urogenital system cancers, delve into related targeted therapy strategies, and discuss future research directions, with the goal of offering valuable insights for researchers in this field.